Hubungan Pemanfaatan Aplikasi Kalender Menstruasi dengan Pengetahuan Catin Mengenai Cara Memperkirakan Masa Subur di KUA Kecamatan Klojen Kota Malang - Citra Nur Imania; Herawati Mansur (JURNAL BIDANG ILMU KESEHATAN, 2026)
Many prospective brides (catin) do not understand how to accurately estimate their fertile period, which raises concerns about unplanned pregnancies. This lack of knowledge is often caused by limited access to information or low utilization of tools such as menstrual calendar apps. Without proper planning, the risk of unwanted pregnancy, fertility issues, and reproductive problems can increase. This study aims to investigate the relationship between the use of menstrual calendar apps and catin's knowledge of how to estimate their fertile period at the KUA (Religious Affairs Office) of Klojen Subdistrict, Malang City. This study employs an analytical correlational design with a cross-sectional approach. The study population consists of 43 female catin at the KUA of Klojen Subdistrict, Malang City, from June 19–24, 2025, with a sample of 39 female catin selected using purposive sampling. Data were collected using a questionnaire. Data analysis utilized the Spearman correlation test. The results show that the majority of female catin have moderate utilization of menstrual calendar applications (48.7%) and most have good knowledge (69.2%). The Spearman statistical test yielded a ρ value of 0.014 (< α = 0.05). With a correlation coefficient of 0.389, indicating a low but positive correlation. This study demonstrates a relationship between the use of menstrual calendar apps and brides to-be's knowledge of how to estimate their fertile period. Therefore, it is hoped that healthcare professionals can enhance brides-to-be's knowledge regarding how to estimate their fertile period through direct education during marriage counseling by utilizing menstrual calendar apps to optimize their knowledge. Menstrual Calendar Application, Knowledge, Fertile Period